Diseño de un circuito gastronómico de la comida típica manabita en el desarrollo turístico del cantón Chone - Muñoz Franco, Lisbeth Alexandra (2016)
The present research aims the design of a typical manabita gastronomic circuit in Chone canton; the theoretical framework was elaborated to endorse the study. The methodology applied consists of four phases, first phase elaborated the tourist diagnosis in which there were identified the tourist potential attractions; the current situation of the manabita gastronomy and the quality of tourist infrastructure in the canton was inventory and analyzed with a SWOT matrix. During the development the second phase profiled the visitor identifying the characteristics of the demand and tourist offering. Third phase designed the gastronomic circuit created in order to adapt the needs, interest and expectations of potential tourist. Later, strategies for commercialization were established by means of distribution channels where the gastronomic circuit will be promoted. This type of activities incite the socioeconomic development of the canton and improve the quality of life of their citizens.